Is additive manufacturing of patient-specific implant is beneficial for orthopedics - Aleena Ariz; Ilma Tasneem; Devyani Bharti; Abhishek Vaish; Abid Haleem; Mohd Javaid (Apollo Medicine)
Purpose: Additive manufacturing (AM), mostly referred to as three-dimensional (3D) printing that has the potential to accelerate innovation, minimize materials and energy usage, compress supply chains, and reduce waste. Due to its extensive capability, its applications in orthopedics are enormous. The purpose of this article is to explore the application of this technology for patient-specific implants to improve the functional outcomes of orthopedics' patients. Methods: A brief review of AM and its applications in orthopedics are performed. In this process, we capture the data of the patient using computed tomography scan. Patients' data in 3D format are analyzed by the customized software before being printed by the fused deposition modeling 3D printing technology. A case study with a patient has helped in understanding the benefits. Results: 3D printed, patient-specific models help for understanding the proper planning of the surgery. AM-based processes provided a fast, cost-effective, and efficient solution during the planning of the surgery. Conclusion: 3D printers print any required product from a digital 3D object. The part is manufactured layer by layer, using different materials such as metal, plastic, nylon, and over a hundred other materials. AM allows us to manufacture complicated shapes with much less material and quickly. It is useful in sectors such as manufacturing, industrial design, jewelry, architecture, engineering and construction, aerospace, automotive, dental and medical industries, education, geographic information systems, civil engineering, and many others. The applications of this technology are increasing in orthopedics from surgical planning to actual surgery. The surgical planning undertaken at the clinic helped a musician. The patient returned to the activities of daily living in 3 weeks with a full range of motion, and after 3 months, he was able to play his musical equipment.